## phury 2 years ago solve using substitution, show work -4x + y = 6 -5x - y = 21

1. KAOS|abdullah

find x in terms of y in 1st eqn. ,substitute in the 2nd eqn. and u get the value of y...equate that and u get the value of x

2. phury

example?

3. shaik0124

|dw:1358532187958:dw|

4. phury

i am sorry, i have no idea what that says.

5. KAOS|abdullah

take 2 any equations like 2x+3y=11---(1) and 3x+5y=12----(2) .....from (1) u can find that x=(11-3y)/2...substitute this x value in eqn. (2) and solve...u'll get the value of y

6. shaik0124

-9x-27=0 -9x=27 x=-3 now u get y by substuting x value in any one of the equations

7. KAOS|abdullah

and then substitute that value of y in eqn (1) or (2) and get the value of x

8. phury

i understabd substituting the final value, i just have to get it first. i dont know how to solve -4x + y = 6

9. shaik0124

what i have done is i got the value of y from 2nd equation and substituted in first so by substituting y in 1st equation u will get equation in x terms from u will get x value and substitute x value in any equation and get y

10. shaik0124

just add+4x on both sides then u will get y|dw:1358532633268:dw|

11. phury

yeah, i got y = 6 + 4x

12. shaik0124

now u substitute y value in the other equation and u will get the equation in x terms ok do this

13. phury

-5x + 6 + 4x

14. phury

-5x + 6 + 4x = 21 -1x + 6 = 21 -1x = 15 x = -15 ?

15. shaik0124

no it is -5x+4x-6=21 now solve

16. shaik0124

|dw:1358533659839:dw|

17. phury

move the 6 and 4x and the operation changes? thought i forgot something -5x + 4x - 6 = 21 -1x - 6 = 21 -1x = 26 x = -26

18. shaik0124

19. phury

thanks alot (:

20. shaik0124

now u substitute x value in any equation u will get y value

21. phury

-4 (-26) + y = 6 104 + y = 6 y = 98

22. shaik0124